Endovenous Management of Varicose Veins. (May 2019) - Belramman, Amjad; Bootun, Roshan; Lane, Tristan R. A.; Davies, Alun H.
Varicose veins are a very common condition and have been the subject of a recent proliferation of treatment modalities. The advent of the endovenous treatment era has led to a confusing array of different techniques that can be daunting when making the transition from traditional surgery. All modalities offer excellent results in the right situation, and each has its own treatment profile. Thermal ablation techniques have matured and have a reassuring and reliable outcome, but the arrival of nonthermal techniques has delivered further options for both patient and surgeon. This article provides an overview of the different treatment devices and modalities available to the modern superficial vein surgeon and details the currently available evidence and summation analysis to help surgeons to make an appropriate treatment choice for their patients.